An In Vitro Study on the Antimicrobial Effect of Fumigation with Jatu-Sarjarasadi Choorna (International Journal of Ayurveda and Pharma Research, 2024)
In the present scenario, shooting incidence of airborne diseases is a major public health challenge. Therefore, disinfecting our immediate surroundings is quite important. In Ayurveda, Dhoopana is a disinfection method by which drugs of herbal, herbo-mineral or animal origin are used for fumigation. It is a safe, natural and cost-effective method for disinfection. But the effectiveness of Dhoopana has to be proved scientifically for the acceptance of the modern society. Therefore, Jatu-sarjarasadi dhoopa yoga mentioned in Ashtanga samgraha sutrasthana is selected for the study to evaluate its antimicrobial activity. Jatu, Sarjarasa, Ushira, Sarshapa, Patra, Valaka, Vella, Arushkara, Pura, Arjuna are the ten ingredients of the yoga, among which Arushkara is replaced in this study with its Abhava dravya Citraka due to safety reasons. The study was conducted in the procedure room of Prasootitantra Department of Government Ayurveda College Hospital, Tripunithura. The room was fumigated for 30 minutes and kept enclosed for 24 hours. Total microbial colonies were estimated by settle plate method. Petridishes containing culture medium of bacteria and fungi were exposed for 60 minutes in the room before fumigation and 24 hours after fumigation. The sample plates were incubated and total microbial colonies before and after fumigation were counted. The data was statistically analysed using Wilcoxon Signed Rank Test. On statistical analysis, the reduction in total colony count of bacteriae and fungi was found to be significant and showed profound anti-bacterial activity when compared to anti-fungal action. The study concluded that fumigation with Jatu-sarjarasadi choorna has anti-microbial effect.